The Influence of Feeding Practice on the Risk of Stunting in Toddler: A Scoping Review - Sholihah Gustavia Yolanda; Ismarwati Ismarwati (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
Child stunting is a serious case that is difficult to overcome because it is caused by poor food quality and the amount of food that does not meet the body's needs during the first two years of life. The purpose of this study is to review the influence of feeding practices and feeding methods on the risk of stunting in children under five. PRISMA-ScR reporting guidelines are used to identify key concepts and knowledge gaps. This scoping review used a five-step framework approach. The databases used were PubMed, Wiley Online Library, ScienceDirect, and EBSCO. Manual searches used the Research Rabbit search engine. Based on the search results of 979 articles, ten articles were found that matched the inclusion criteria. Out of the seven themes found, four were in line with WHO's complementary feeding indicators, namely Minimum Meal Frequency (MMF), Minimum Dietary Diversity (MDD), Minimum Acceptable Diet (MAD), and Introduction of Solid, Semi-Solid or Soft Foods (ISSSF). While the other three themes are a time of first feeding, breastfeeding practices, and feeding methods. Overall, inadequate feeding practices result in child malnutrition, including stunting. Improper nutrition and care during the first 1000 days of birth is detrimental to a child's life, both in the short and long term as malnutrition that occurs at this early stage of life has serious and irreversible consequences. Large-scale studies are recommended to explore the role of IYCF in reducing stunting and qualitative studies to determine barriers and drivers to improve infant and young child feeding practices.